ANALISIS DISIPLIN KERJA KARYWAN DALAM MENGANTISIPASI KECELAKAAN KERJA DI PT. MULTI HIDRACHROME INDUSTRI - Raditya Alvinnanda (2021)
This study aims to analyze the implementation of employee discipline and identify the factors that influence employee discipline at PT. Industrial Multi Hydrachrome. The research method used is a qualitative approach with phenomenological studies. Data was collected by observation, interviews, and documentation. The results of the study indicate that PT. Multi Hidrachrome Industri has implemented preventive discipline, corrective discipline, and progressive discipline, but there are still shortcomings in its implementation such as selecting the best employees, installing disciplinary posters, and procuring Personal Protective Equipment (PPE). The factors that influence discipline at PT. MHI includes the existence of definite rules, exemplary leadership, leadership supervision, leadership courage to take action, leadership relationships with employees and habits that are often carried out.